PENINGKATAN HASIL BELAJAR LUAS BANGUN DATAR MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING PADA SISWA KELAS III SD NEGERI 51/II DESA PAKU AJI KECAMATAN TANAH SEPENGGAL LINTASKABUPATEN BUNGO - Randi Eka Putra (LP3M STKIP Muhammadiyah Muara Bungo, 2018)
Broad flat learning in SDN 51/ II students in Paku Aji Village is still conventional. Learning is still teacher-centered, making it boring for students. For this reason, researchers are interested in improving the learning process of mathematics, especially in the area of square and rectangular learning through the Contextual Teaching and Learning (CTL) approach. The CTL approach is felt to be able to overcome existing problems. In improving the learning outcomes of square and rectangular areas through the CTL approach there are 7 steps, namely: constructivism, inquiry, asking questions, learning society, modeling, reflection and authentic assessment. The results of the study conducted the percentage of the average class of student learning outcomes in the first cycle of meeting 1 with the material square area is 80% in the first cycle of meeting 2 with rectangular material is 69%, cycle II meeting 1 with the material area square and rectangle is 97 % in the second cycle of meeting 2 was 98%. The conclusion obtained from this study is that the CTL approach can improve the learning outcomes of a flat building area, which is about the area of a square and a rectangle.